2023
DOI: 10.1021/acs.jcim.3c00409
|View full text |Cite
|
Sign up to set email alerts
|

AI-Driven Discovery of SARS-CoV-2 Main Protease Fragment-like Inhibitors with Antiviral Activity In Vitro

Abstract: SARS-CoV-2 is the causative agent of COVID-19 and is responsible for the current global pandemic. The viral genome contains 5 major open reading frames of which the largest ORF1ab codes for two polyproteins, pp1ab and pp1a, which are subsequently cleaved into 16 nonstructural proteins (nsp) by two viral cysteine proteases encoded within the polyproteins. The main protease (Mpro, nsp5) cleaves the majority of the nsp’s, making it essential for viral replication and has been successfully targeted for the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 86 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…For example, Saramago et al have identified three potent molecules with anti-SARS-CoV-2 activity through an AI-driven approach followed by in vitro validation [ 92 ]. This was achieved by training a recurrent neural network (RNN) to design textual representations of molecules through the simplified molecular-input line-entry system (SMILES) and then fine-tuning the model towards the generation of fragment-like molecules with potential activity against SARS-CoV-2 M pro .…”
Section: Inhibition Of Viral Proteases By Targeting the Active Sitementioning
confidence: 99%
“…For example, Saramago et al have identified three potent molecules with anti-SARS-CoV-2 activity through an AI-driven approach followed by in vitro validation [ 92 ]. This was achieved by training a recurrent neural network (RNN) to design textual representations of molecules through the simplified molecular-input line-entry system (SMILES) and then fine-tuning the model towards the generation of fragment-like molecules with potential activity against SARS-CoV-2 M pro .…”
Section: Inhibition Of Viral Proteases By Targeting the Active Sitementioning
confidence: 99%